4-aminopyridine restores visual ocular motor function in upbeat nystagmus. Issue 3 (16th February 2005) - Glasauer, S; Kalla, R; Büttner, U; Strupp, M; Brandt, T
Abstract : The effect of the potassium channel blocker 4-aminopyridine (4-AP) on spontaneous upbeat nystagmus (UBN) was investigated with the search coil technique during fixation in different gaze positions and smooth pursuit in a patient before and after ingestion of 10 mg 4-AP. UBN was reduced from 8.6 deg/s to 2.0 deg/s by 4-AP causing subjective relief from distressing oscillopsia, and impaired upward smooth pursuit was restored (gains: before medication 0.38; after medication 0.86). In the dark, UBN was slightly stronger and not affected by 4-AP. We propose that 4-AP improved the function of cerebellar pathways that mediate gaze holding and smooth pursuit by intensifying the excitability of cerebellar Purkinje cells.